The remembrance of Rwanda's Genocide and its effects on the democratic present: An analyses out of mediatic necropolitics - Acerbi, Júlia dos Santos (2021)
This paper aims to analyze the influence of the narratives disseminated during the Rwandan genocide (1994) on the present democratic situation of the country. Thus, the article uses bibliographical research as methodology, followed by a qualitative approach, in order, firstly, to analyze the events that caused the episode and its consequences, as well as the concept of genocide itself. Subsequently, an analysis will be made of the role of the media as a vector of narratives that instigated polarization throughout the Rwandan Genocide. And finally, the remembrance of such 20th century episode and how the effects of this process hinder democratic progress in the country will be verified. To carry out such a study, Achile Mbembe’s concept of necropolitics will be used as theoretical contribution.